Diagnostic accuracy of frozen section in Central nervous system lesions, a 10-year study. - KHODDAMI*, Maliheh; AKBARZADEH, Ali; MORDAI, Afshin; BIDARI-ZEREHPOUSH, Farahnaz; ALIPOUR, Hamid; SAMADZADEH, Sara; ALIPOUR, Bijan (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Khoddami M, Akbarzadeh A, Mordai A, Bidari Zerehpoush F, Alipour H, Samadzadeh S, Alipour B.Diagnostic Accuracy of Frozen Section of Central Nervous System Lesions: A 10-Year Study. Iran J Child Neurol. 2015 Winter;9(1):25-30. Abstract Objective Definitive diagnosis of the central nervous system (CNS) lesions is unknown prior to histopathological examination. To determine the method and the endpoint for surgery, intraoperative evaluation of the lesion helps the surgeon. In this study, the diagnostic accuracy and pitfalls of using frozen section (FS) of CNS lesions is determined. Materials & Methods In this retrospective study, we analyzed the results of FS and permanent diagnoses of all CNS lesions by reviewing reports from 3 general hospitals between March 2001 and March 2011. Results 273 cases were reviewed and patients with an age range from 3 to 77 years of age were considered. 166 (60.4%) had complete concordance between FS and permanent section diagnosis, 83 (30.2%) had partial concordance, and 24 cases (9.5%) were discordant. Considering the concordant and partially concordant cases, the accuracy rate was 99.5%, sensitivity was 91.4%, specificity was 99.7%, and positive and negative predictive values were 88.4% and 99.8%, respectively. Conclusion Our results show high sensitivity and specificity of FS diagnosis in the evaluation of CNS lesions. A Kappa agreement score of 0.88 shows high concordance for FS results with permanent section. Pathologist’s misinterpretation, small biopsy samples (not representative of the entire tumor), suboptimal slides, and inadequate information about tumor location and radiologic findings appear to be the major causes for these discrepancies indicated from our study. References Taxy JB, Anthony G. Biopsy interpretation: the frozen section. 1st ed. China: Lippincott Williams & Wilkins; 2010. P.301-3. Somerset HL, Kleinschmidt-DeMasters BK. Approach to the intraoperative consultation for neurosurgical specimens. Adv Anat Pathol 2011; 18:446-9. doi: 10.1097/ PAP.0b013e3182169934. Regragui A, Amarti Rifﬁ A, Maher M, El Khamlichi A, Saidi A. Accuracy of Intraoperative diagnosis in central nervous system tumors: report of 1315 cases. Neurochirurgie 2003; 49(2-3 Pt 1):67-72. Plesec TP, Prayson RA. Frozen section discrepancy in the evaluation of central nervous system tumors. Arch Pathol Lab Med 2007; 131:1532-40. Savargaonkar P, Farmer PM. Utility of intra-operative consultations for the diagnosis of central nervous system lesions. Ann Clin Lab Sci 2001; 31:133-9. Talan-Hraniloviæ J, Vuèiæ M, Ulamec M, Belicza M. Intraoperative frozen section analysis in of the central nervous system and pituitary gland pathology. Acta Clin Croat 2005; 44:217-21. Roessler K, Dietrich W, Kitz K. High diagnostic accuracy of cytologic smears of central nervous system tumors. A 15-year experience based on 4,172 patients. Acta Cytol 2002; 46:667-74. Ud Din N, Memon A, Idress R, Ahmad Z, Hasan S. Central Nervous System Lesions: Correlation of Intraoperative and Final Diagnoses, Six Year Experience at a Referral Centre in a Developing Country, Pakistan. Asian Pac J Cancer Prev 2011; 12:1435-7. Burger PC, Scheithauer BW. Tumors of the Central Nervous System. In: AFIP Atlas of Tumor Pathology Series 4. Washington DC: American Registry of Pathology; 2007. Louis DN, Ohgaki H, Wiestler OD, Cavenee WK, Burger PC, Jouvet A, et al. The 2007 WHO Classification of Tumours of the Central Nervous System. Acta Neuropathol. 2007; 114: 97–109. doi: 10.1007/s00401- 007-0243-4